THERAPEUTIC MANAGEMENT OF ENTEROLITHS IN A MARE-A CASE REPORT - Hadiya, KK; Borakhatriya, DN; Buhecha, VK; Mungad, KS; Kalasariya, RM (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Acute abdominal pain in the horse is one of the most common emergency in equine practice. Irritation or obstruction of the gastrointestinal tract is caused by excessive geosediments,which leads to chronic diarrhoea, weight loss and colic (Husted et al., 2005). Equines, particularly grazing ones, are more prone to sand colic, sand impaction and enteroliths (Colahan, 1987; Hassel, 2002).The most devastating aspect of this condition is the potential for pressure necrosis and rupture of the intestinal tract (Hassel, 2002). Clinical signs vary in horses with sand impactions and are similar to the signs resulting from impactions of the large colon by ingesta (Synder and Spier, 1996). Mild cases of sand colic are commonly treated with non-steroidal anti-inflammatory drugs, mineral oil, dioctyl sodium sulfosuccinate, magnesium sulphate and psyllium mucilloid (Landes et al., 2008).